2010
DOI: 10.4191/kcers.2010.47.5.445
|View full text |Cite
|
Sign up to set email alerts
|

Bloating Mechanism of Artificial Lightweight Aggregate for Recycling the Waste Glass

Abstract: The purpose of this study is to improve recycling rate of the waste glasses by investigating bloating mechanism. In this study, we use waste glass(W/G) and hard clay(H/C) as raw materials. The artificial lightweight aggregates were formed by plastic forming(φ=10 mm) and sintered by fast firing method at different temperatures(between 700 and 1250 o C). The physical properties of the aggregates such as bulk specific gravity, adsorption and microstructure of surface and cross-section are investigated with the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Studies of sintering variables have been conducted worked various methods. Different studies have investigated various sintering methods, including rapid sintering [10,11], two-step sintering [12], and normal sintering [1,13]. Riley [1] reported that most clays were expanded by rapid sintering, and defined the chemical composition for the production of lightweight aggregates through the normal sintering process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of sintering variables have been conducted worked various methods. Different studies have investigated various sintering methods, including rapid sintering [10,11], two-step sintering [12], and normal sintering [1,13]. Riley [1] reported that most clays were expanded by rapid sintering, and defined the chemical composition for the production of lightweight aggregates through the normal sintering process.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [12] undertook two-stage sintering by dividing the dry section and the sintering section and then established the bloating conditions of lightweight aggregates with a bulk density of less than 1.0. Kang et al [13] obtained a lightweight aggregate with a low water absorption ratio and density level through normal sintering, and used the rapid sintering method in a study of lightweight aggregates with many types of waste added [10,11]. According to a report by Kaz'mina et al [14], it was confirmed that glass becomes bloated at a specific viscosity during the production of foamed glass, revealing that viscosity is an important aspect of bloating.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of calcining methods have been used, and the methodology for producing aggregates has not been well addressed. In general, lightweight aggregate is lightened by bloating when it is fired, and it requires generation of gas for foaming and surface which can collect the formed gas [19,20]. e bubbling gas is generated by the oxidation of the organic matter and carbon existing inside the reducing atmosphere, where the reaction with external oxygen is blocked during the aggregate firing [21].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, research for the viable methods to reuse the waste becomes an urgent task to be investigated. [1][2][3][4][5] Domestically, various reports on the coal ash recycling and its feasibility study are available that include; for uses as a concrete admixture mainly utilizing the fly ash, as a filler material for road pavement, and as an aggregate for cement mortar replacing the smaller portion of aggregates. We have also involved in researches on the coal ash recycling, and recently, have extended our focus to the industrial wastes recycling especially for manufacturing of artificial lightweight aggregates (ALWA).…”
Section: Introductionmentioning
confidence: 99%
“…Various researches on the waste treatments include; the property improvement of ALWA with the additions of fluxes 3) , the feasibility study for ALWA for concrete by utilizing industrial wastes 4) , the manufacturing method of ALWA using the reclaimed ash from thermal power plants 6) , the sintered properties of ALWA prepared from coal ash and limestone 7) , etc. These studies contributed for the reuses of waste materials and established its technical methods.…”
Section: Introductionmentioning
confidence: 99%